2006
DOI: 10.1017/ber2006464
|View full text |Cite
|
Sign up to set email alerts
|

Geographic biotype and host-associated local adaptation in a polyphagous species, <I>Lambdina fiscellaria</I> (Lepidoptera: Geometridae) feeding on balsam fir on Anticosti Island, Canada

Abstract: The debate about mechanisms underlying the evolution of host specialization by herbivorous insects remains open. Natural selection may act locally and lead to different patterns of geographic variation in life history traits of polyphagous herbivores. The hypothesis of genetically-based trade-offs in offspring performance on different hosts has been proposed but this has rarely been demonstrated. Under laboratory conditions, the biological performance of two populations of the hemlock looper Lambdina fiscellar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…Biotypic variations within species have been extensively described in whiteflies and aphids. Biotypic variation has been related to insecticide resistance (Horowitz et al 2005), host range (Dolatti et al 2005;Hebert et al 2006), plant physiological disorders induced by the insect (Yokomi et al 1990) or differential fitness (Jyoti and Michaud 2005). These differences tend to persist when several biotypes are brought in sympatry, suggesting at least partial reproductive isolation among them; however the exact degree of isolation is usually unknown (Diehl and Bush 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Biotypic variations within species have been extensively described in whiteflies and aphids. Biotypic variation has been related to insecticide resistance (Horowitz et al 2005), host range (Dolatti et al 2005;Hebert et al 2006), plant physiological disorders induced by the insect (Yokomi et al 1990) or differential fitness (Jyoti and Michaud 2005). These differences tend to persist when several biotypes are brought in sympatry, suggesting at least partial reproductive isolation among them; however the exact degree of isolation is usually unknown (Diehl and Bush 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Other species of Abies are grown in the PRA area, often for Christmas tree production. Within the laboratory, L. fiscellaria fiscellaria first‐instar larvae have been reared successfully on foliage from a number of hosts that the pest has also been recorded on in the wider environment (Carroll, ; Hérbert et al ., ). Though the pest shows a preference for A. balsamea in its native range, it clearly has some ecological plasticity on host choices.…”
Section: Introductionmentioning
confidence: 97%
“…A study of the cytochrome oxidase I and II genes of mitochondrial DNA (mtDNA) for three subspecies of L. fiscellaria [ L.f. fiscellaria , L.f. lugubrosa (Hulst), L.f. somniaria (Hulst)] indicated some genetic polymorphism between subspecies but did not clearly differentiate subspecies (Sperling et al , 1999). Two geographic ecotypes of L.f. fiscellaria are recognized in eastern North America, of which the northern ecotype undergoes four larval instars and the southern ecotype undergoes five larval instars (Hébert et al , 2006; Berthiaume, 2007). Laboratory experiments have confirmed that this trait is fixed through rearing the two ecotypes under the same environmental conditions, in which the ecotypes maintained their respective number of larval instars (Berthiaume, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Additional significant differences in life‐history traits include: (i) faster development of the four‐instar ecotype compared to the five‐instar ecotype; and (ii) lower fecundity but greater egg size in the four‐instar ecotype (Berthiaume, 2007). It has been hypothesized that these traits are an adaptation to the latitudinal difference in climate in which these ecotypes reside (Hébert et al , 2006; Berthiaume, 2007). The most serious outbreaks have been reported from the northern parts of the range of the hemlock looper (Martineau, 1984) and are therefore of higher concern from a pest management perspective.…”
Section: Introductionmentioning
confidence: 99%